技術及職業教育政策之接受度：實踐研究新視角 Policy Acceptance of Technical Vocational Education: A Perspective From a New Act on Field Study - 洪榮昭 Jon-Chao Hong; 葉建宏 Jian-Hong Ye; 范靜媛 Jing-Yun Fan (National Taiwan Normal University, 2019)
為落實技術及職業教育人才的實作能力，臺灣於 2015 年 1 月 14 日公布《技術及職業教育法》之後，依該法第 25 條及第 26 條規定，技職校院專業科目或技術科目之教師須定期赴業界研習或研究，但目前此類教師參與研習與研究人數仍然偏低，因此，引發本研究探討此議題之動機。本研究以調查研究法，透過立意抽樣方式蒐集資料，邀請技職校院專業科目或技術科目之教師與技職校院師資培育生為研究對象，有效參與者為 244 人；並根據推拉因素 與期望價值建構技術及職業教育政策接受度與意願之模式，運用驗證性因素分析及結構方程模式檢定研究假設。研究結果顯示：科技與產業的推力及拉力對於消弭學用落差的感知價值呈現正相關，但消弭學用落差的感知價值對於政策的配合意願卻呈現負相關。研究結果發現，認知與行為意願有落差，易造成徒法無以執行。因此，本研究建議教育主管機關提供更多的獎勵機制，以提升技職校院專業科目或技術科目之教師配合政策之意願。 Since the introduction of the Technical and Vocational Education Act (hereinafter "TVE Act") in Taiwan in 2015 under Articles 25 and 26, technical teachers are required to pursue advanced study or research in the industrial field. However, few technical teachers are willing to abide by this policy, which eliminates the difference between learning and practice. This study conducted a survey by collecting data from 244 teachers of technical skills or subjects in technical vocational colleges. The results indicate that pull and push factors were positively related to the perceived value of the TVE Act, whereas the perceived value of the TVE Act was negatively related to their intention of implementation. Feedback from some of the research participants indicates that the mandatory policy of the regulation may be one of the factors leading to the exclusion of the policy. the result, this study suggested that the education policy should not only stipulate teachers' obligation to do research or only to learn from its profession, but incentives also need to be provided as a push factors to attract technical teacher's intention to follow the policies, so that professional or technical subjects in technical vocational schools can be improved.